A Descriptive Study of Family Planning Services and Their Outcome in A Tribal Area of South Gujarat - Hetav B Sadadiwala; Abhay Kavishvar; Naresh T Chauhan; Gaurishankar B Verma; Tarlika C Chaudhari (Medsci Publications, 2015)
Introduction Tapi district is one of the Tribal district of the Guja- rat state having lower crude birth date (CBR) (15.2 per 1000 live births), higher crude death rate (CDR) (6.1 per 1000 population) and variable total fertility rate (TFR). This study was conducted to analyze the activities under National Family Welfare Programme especially tubal ligation operations and cupper T insertion and to disseminate the findings to executive authorities to relook over the data and situation. Material and method: Data compiled from various records of Maypur Primary Health Centre and annual report from Registrar of State Births and Death Registration analyzed on MS Excel. Results: Only 57 persons were added in the PHC area in a year as a result of reasonable coverage with tubal ligation and Copper T- 380A. Coverage of family welfare services showed higher achievement in permanent method (1.3:1, Tubal ligation: Copper T-380A) overall ratio of permanent versus spacing method (0.5:1, Tubal ligation: Copper T-380A) reported for Gujarat. Conclusion: there is a need to look into data meticulously and set strategies in a way that it preserves rational of Family Welfare Programme with changing demographic profile in a smaller region. Recommendations: In a restricted indigenous communities, authority shall address the evidence based need, the desire of the couple and the cost of National Family Welfare Programme.